MEDIA BONEKA TANGAN DAPAT MENINGKATKAN KETERAMPILAN MENYIMAK ANAK USIA 5-6 TAHUN DENGAN METODE BERCERITA - Wulandari, Rizki; Nursyamsiyah, Siti; Akhyadi, Ade Sadikin; Jumiatin, Dedah Jumiatin; Sumitra, Agus (IKIP Siliwangi, 2019)
One from of ability to tell stories is the listening process.in general, older brothers still have difficulty listening to and unerstanding the stories that the teacher conveyed, one of conditions is the influence of the teacher’s low creativity in determining the medium of learning to tell childeren. On the other hand children are still less focused and often talk to themselves with their friends so that children do not concentrate and listen to the explanation from the teacher, this happens to the child and during the learning process. This phenomenon is a problem that needs to be found as an alternative solution. One methode that can be used is the storrytelling methode using hand puppet media. This study used a classroom action research methode which numbered 12 children. The results obtained from 12 children are significant, no children are undeveloped, if the value is obtained, it is 0 percent, 1 child begins to develop, if the value is obtained, it is8%, 4 children have developed as expected or if the value is obtained, it is 32%, and 7 children develop very well or if the value is obtained, its is 60%. From the percentage accumulated there was an average increase of 33%. According to the results of improvement in each cycle, the use of hand puppet media on story telling techniques can influence the listening skills of group B children in this kindergarten. From tehe data obtained it can be concluded that the media of hand puppets can improve the listening skill of children.Keywords: Listening Skill, tell stories, Hand Puppet